Designing a QRIS Management Application to Simplify Digital Transactions Using the Prototype Method - Ami Abdul Jabar; Darmeli Nasution (Yayasan Sinergi Multidimensi Kreatif, 2024)
In the digital era, financial transactions are increasingly dependent on information technology, particularly through the use of QRIS (Quick Response Code Indonesian Standard) developed by Bank Indonesia. This study aims to design a QRIS management application that facilitates business owners in efficiently managing various QR codes. The prototype method is used to describe the system to be developed, including QRIS data management, dynamic QR code generation, and structured database design. The design results show that this application can address issues related to cluttered displays caused by the use of multiple QRIS stickers, simplify the transaction process for consumers, and enhance the professionalism of merchants. Therefore, this application design is expected to contribute significantly to the efficiency of digital transactions and lay the groundwork for the development of more advanced applications in the future.